Learning Development Oriented on Character Education Strengthening - Sri Mulyanti (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2019)
This article describes the development of learning steps oriented towards strengthening character education. The material used in learning is "Text Report Experiments". The development of learning steps is prepared to provide convenience to Indonesian language teachers in formulating the lesson plan and in implementing it in the classroom. The research uses a development method that focuses on efforts to produce and validate a learning model, especially learning implementation activities that are in the lesson plan made by Indonesian language teachers Class IX. The products developed in the study are steps in Indonesian language learning especially with regard to text reporting experiments. The results of the study were in the form of developing learning steps in detail and contained the values of strengthening character education. The results of the study are expected to facilitate teachers in carrying out Indonesian language learning and also facilitate in preparing lesson plans. In addition, learning Indonesian using this development model is expected to encourage students to have good communication competencies and character. Keywords: learning steps, lesson plan, character education.